Scaffold Seeking: A Reverse Design of Scaffolding in Computer-Supported Word Problem Solving. (December 2015) - Cheng, Hercy N. H.; Yang, Euphony F. Y.; Liao, Calvin C. Y.; Chang, Ben; Huang, Yana C. Y.; Chan, Tak-Wai
Although well-designed scaffolding may assist students to accomplish learning tasks, its insufficient capability to dynamically assess students' abilities and to adaptively support them may result in the problem of overscaffolding. Our previous project has also shown that students using scaffolds to solve mathematical word problems for a long time may regard problem solving as a repetitive job and eventually became bored. To avoid the problem, this study redesigns the activity model of scaffolding by adopting a reverse rationale and incorporating the concept of helps seeking. Furthermore, this study proposes the activity model of scaffold seeking and designs a system that empowers students to seek scaffolds for solving mathematical word problems. A case study shows that the model may encourage students to solve problems by themselves rather than abusing scaffolds. Besides, the result also suggests that students are potential to express their thinking without the limitation of scaffolds.